THE ROLE AND MUTUAL INTEGRATION OF CAD, CAE, AND CAM SYSTEMS IN MECHANICAL ENGINEERING - Yo’ldashev Bilolxon Iqboljon o’g’li (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract The contemporary development of mechanical engineering is inseparable from the progressive convergence of Computer-Aided Design (CAD), Computer-Aided Engineering (CAE), and Computer-Aided Manufacturing (CAM) into a unified digital environment capable of supporting the full product lifecycle from concept generation to production planning, machining, inspection, and subsequent optimization. The scientific and practical relevance of this topic lies in the fact that traditional drawing- based and document-fragmented workflows no longer provide adequate speed, traceability, or accuracy for modern manufacturing systems that must operate under conditions of mass customization, compressed development cycles, rising quality expectations, and increasing integration between physical and digital production assets. In a model-based enterprise, digital models are not passive geometric representations but authoritative information carriers that connect design intent, simulation data, process planning, manufacturing semantics, and quality assurance. This article analyzes the role of CAD, CAE, and CAM systems in mechanical engineering and examines the mechanisms, benefits, and constraints of their integration within contemporary product realization environments. The study is based on a structured analytical review of standards documents, NIST technical publications, and recent scholarly literature on model-based definition, digital thread architectures, CAD-to- CAE interoperability, feature recognition, process knowledge representation, and digital twin applications in machining. The results show that effective CAD–CAE– CAM integration improves consistency of engineering data, reduces design-to- manufacturing cycle time, strengthens product quality, enables earlier manufacturability assessment, supports more reliable process planning, and provides the informational backbone for digital thread and digital twin implementation. At the same time, the review reveals persistent obstacles, including semantic gaps between design and manufacturing representations, incomplete interoperability, standards implementation costs, skills shortages, fragmented knowledge structures, and the continuing coexistence of model-based and drawing-based workflows. It is concluded that the most productive direction for mechanical engineering enterprises is not the isolated improvement of CAD, CAE, or CAM modules separately, but the establishment of model-centric, standards-based, and semantically rich integration architectures in which a single authoritative product definition can be reused across design, analysis, planning, machining, inspection, and lifecycle feedback. The scientific novelty of the article lies in presenting CAD, CAE, and CAM not as separate software categories, but as functionally interdependent layers of a unified digital manufacturing logic whose maturity increasingly depends on standards such as STEP AP242, model-based definition, manufacturing feature semantics, and digital thread continuity. The practical significance of the article lies in identifying a realistic framework for universities, industrial enterprises, and engineering teams seeking to improve mechanical product development efficiency through deeper CAx integration.